OVERCROWDED CLASSROOMS IN THE ANALYSIS OF TEACHER-STUDENTS INTERACTION - Indra Sudrajat; Purnamasari, Nia (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
The study was carried out to find out the most serious problems faced by the teachers-student interaction in overcrowded classes The aims in this study is to investigate the effect of teacher-students interaction in overcrowded classroom. This study focuses particularly on the problems that are being faced by both teachers and students while teaching-learning process. The method of this research work is qualitative method. The data were gathered through self-completion questionnaires and interview administered to 33 student and four teachers for questionnaire. Questionnaire for teacher is to understand more fully how teachers think about overcrowded classrooms as well as about classroom interaction, also to gain through overview about what the relationship between crowded classes and teacher-student interaction, and for student is to understand more fully whether overcrowded classes have an effect on teacher-student interaction, a short questionnaire was designed to gather opinion. In order to support the questionnaire, the students and the teacher were interviewed through a sequence of questions related to the causes of classroom interaction and overcrowded classroom to find out the effect of teacher-student interaction in overcrowded classroom. The study involved three students based on the high, middle and low value in English classroom and two teachers in the interview at a private senior high school in Bandung. The results of this study showed the main problems being faced in overcrowded classes including noise making, lack of individual attention and classroom arrangement are issues that influence interaction in the class. Based on the result we can saw that Teacher-Student Interaction is affected by the number of Student.